Characterization of Solitary Lesions in the Extremities on Whole-Body Bone Scan in Patients With Known Cancer: Contribution of Single-Photon Emission Computed Tomography/Computed Tomography - Peng, Hao; Zhang, Linqi; Zhou, Tao; Li, Wei; Li, Wen; Ma, Liwu; Zhang, Rusen (Frontiers in Oncology, 2019)
Background: Solitary lesions in the extremities showing 99mTc-methylene diphosphate (MDP) uptake are often encountered on whole-body bone scan (WBS), and proper interpretation of this diagnostic method is important for patients with known cancer. The purpose of this study was to summarize the characteristics of solitary lesions in the extremities of patients with known cancer and to evaluate the diagnostic accuracy of single-photon emission computed tomography/computed tomography (SPECT/CT) in differentiating bone metastases from benign bone lesions. Methods: This study was a retrospective review of 86 patients (54 males and 32 females; mean age, 57.88 ± 10.97 years; range, 31–81 years) with known cancer who underwent WBS and showed solitary lesions with 99mTc-MDP uptake in the extremities and then underwent SPECT/CT for further diagnosis. SPECT/CT images were independently interpreted by two experienced nuclear medicine physicians. The diagnostic accuracy of SPECT/CT in differentiating malignant from benign solitary lesions in the extremities was evaluated. Inter-reviewer agreement was assessed by using weighted k statistics. The standard diagnostic criterion was based on biopsy or radiologic follow-up over at least 12 months. Results: In total, 23 bone metastases and 63 (73.26%) benign lesions were diagnosed. The majority (16/23, 69.57%) of bone metastases were found in the diaphyses. The most common benign bone disease was a benign bone tumor (31.75%, 20/63). The majority (13/20, 65%) of benign bone tumors were enchondromas. In the proximal and distal extremities, the most common disease was degeneration (27.11%, 16/59), followed by benign bone tumors and osteonecrosis of the femoral head (ONFH) (22.03%, 13/59). In the diaphyses of the extremities, bone metastasis was the most common disease, accounting for 64% (16/25) of the findings. For the SPECT/CT analysis, the accuracy was 94.19% (81/86) for reviewer 1 and 95.34% (82/86) for reviewer 2. The weighted kappa score for inter-reviewer agreement was 0.813. Conclusion: When solitary disease of the extremities is detected by WBS in patients with known cancer, benign lesions may be more common than malignant lesions. SPECT/CT resulted in not only fewer equivocal lesions but also in higher diagnostic accuracy.